La gran minería y su impacto urbano en el siglo XXI: el suelo periurbano como escenario conflictivo en una ciudad intermedia como Cajamarca - Vega-Centeno, Pablo (Pontificia Universidad Católica del Perú, 2025)
During the 20th century, industrial activities linked to the extraction of minerals gave rise to the implementation of settlements or urban neighborhoods as company towns. In the 21st century, mining projects have emerged that focus more on connectivity, which reduces the direct impact on the production of urban spaces. However, its effects on the urban economy can lead to important impacts on urbanization processes. This article analyzes how uncontrolled urban expansion, derived from large-scale mining activity, transforms peri-urban spaces in an intermediate city like Cajamarca: they become scenarios of conflict between rural and urban logic, with changes in land use through notarial means, outside of municipal regulations.

Durante el siglo XX, las actividades industriales vinculadas a la extracción de minerales dieron lugar a la implantación de asentamientos o barrios urbanos a modo de company towns. En el siglo XXI han surgido proyectos mineros que apuestan más por la conectividad, lo que reduce la incidencia directa en la producción de espacios urbanos; no obstante, sus efectos sobre la economía urbana pueden derivar en impactos importantes sobre los procesos de urbanización. El presente artículo analiza cómo una expansión urbana sin control, derivada de una actividad minera a gran escala, transforma los espacios periurbanos en una ciudad intermedia como Cajamarca: se convierten en escenarios de conflicto entre lógicas rurales y urbanas, con cambios de uso del suelo por la vía notarial, al margen de la normativa municipal.
Large mining and its urban impact in the 21st century: The peri-urban land as a conflictive scenario in an intermediate city like Cajamarca
Keywords: Mining; Urbanization; Peri-urban; Cajamarca; Urban economy; Minería; Urbanización; Periurbano; Cajamarca; Economía urbana; https://purl.org/pe-repo/ocde/ford#6.04.08